Grip Strength Decline and Its Determinants in the Very Old: Longitudinal Findings from the Newcastle 85+ Study. - Antoneta Granic; Karen Davies; Carol Jagger; Thomas B L Kirkwood; Holly E Syddall; Avan A Sayer (PLoS ONE)
Background Weak grip strength (GS) is a key component of sarcopenia and frailty and a powerful predictor of mortality, morbidity and disability. Despite increasing interest in understanding GS across the lifespan, little is known about GS decline in the very old (aged ≥85). We examined trajectories of GS in very old adults and identified the determinants. Methods GS (kg) was measured four times over 5 years in 319 men and 526 women participating in the Newcastle 85+ Study. A weak GS sub-cohort was identified as having strength of ≤27 kg (men), and ≤16 kg (women) at baseline and follow-up. Mixed models were used to establish trajectories of GS and associated factors in all participants, men and women, and in those with weak GS. Results Men's mean grip strength was 24.42 (SD = 6.77) kg, and women's 13.23 (4.42) kg (p<0.001) at baseline, with mean absolute change of -5.27 (4.90) kg and -3.14 (3.41), respectively (p<0.001) by 5-year follow-up. In the time-only mixed model, men experienced linear annual decline in GS of -1.13 (0.8) kg (β (SE), p<0.001), whilst women's decline although slower, accelerated by -0.06 (0.02) kg (p = 0.01) over time. In the saturated model, higher baseline physical activity, height, fat-free mass, better self-rated health, and not having arthritis in hand(s) were associated with stronger GS initially in both sexes. Annual GS decline in men and participants with weak GS who were highly physically active was slower by 0.95 and 0.52 kg, respectively compared with inactive counterparts. Conclusion Grip strength decline in the very old followed linear (men) and curvilinear (women) trends. High levels of physical activity were protective of GS loss in men (but not in women) and in those with weak GS. Thus maintaining muscle strength in later life is important to reduce the morbidity and mortality in the very old.